Metodología para el estudio de la pintura mural romana: el conjunto de las musas de Bilbilis - Íñiguez Berrozpe, Lara María (PrimaLun@, 2022)
In this book we present an analysis of one of the ensembles found in Taberna 7 of Domus I (Insula I) at the Roman site of Bilbilis (Calatayud, Zaragoza, Spain), chronologically assigned to 35-45 BC. The importance of this ensemble, colloquially known as the "Muses Ensemble" because of the presence of these figures in the central panels, lies in the fact that it is one of the highest quality ensembles in Hispania. But this book goes beyond the study of a pictorial ensemble and applies to a specific case the methodology that we use in Roman wall painting to work with this material and obtain all the information that is useful from an archaeological point of view.